A systematic review of quality indicators for appropriate antibiotic use in hospitalized adult patients - Marlot C. Kallen; Jan M. Prins (MDPI AG, 2017)
Many quality indicators for appropriate antibiotic use have been developed. We aimed to make a systematic inventory, including the development methodology and validation procedures, of currently available quality indicators (QIs) for appropriate antibiotic use in hospitalized adult patients. We performed a literature search in the Pubmed interface. From the included articles we abstracted i) the indicators developed ii) the type of infection the QIs applied to iii) study design used for the development of the QIs iv) relation of the QIs to outcome measures v) whether the QIs were validated and vi) the characteristics of the validation cohort. Fourteen studies were included, in which 200 QIs were developed. The most frequently mentioned indicators concerned empirical antibiotic therapy according to the guideline (71% of studies), followed by switch from IV to oral therapy (64% of studies), followed by drawing at least two sets of blood cultures and change to pathogen-directed therapy based on culture results (57% of studies). Most QIs were specifically developed for lower respiratory tract infection, urinary tract infection or sepsis. A RAND-modified Delphi procedure was used in the majority of studies (57%). Six studies took outcome measures into consideration during the procedure. Five out of fourteen studies (36%) tested the clinimetric properties of the QIs and 65% of the tested QIs were considered valid. Many studies report the development of quality indicators for appropriate antibiotic use in hospitalized adult patients. However, only a small number of studies validated the developed QIs. Future validation of QIs is needed if we want to implement them in daily practice.